Assessment of the mechanical properties of monolayer graphene using the energy and strain-fluctuation methods. Issue 48 (31st July 2018) - Thomas, Siby; Ajith, K. M.; Lee, Sang Uck; Valsakumar, M. C.
Abstract : Molecular statics and dynamics simulation for the elastic constants of graphene monolayer by the energy and the statistical fluctuation methods. Abstract : Molecular statics and dynamics simulations were performed to investigate the mechanical properties of a monolayer graphene sheet using an efficient energy method and strain-fluctuation method. Using the energy method, we observed that the mechanical properties of an infinite graphene sheet are isotropic, whereas for a finite sheet, they are anisotropic. This work is the first to report the temperature-dependent elastic constants of graphene between 100 and 1000 K using the strain-fluctuation method. We found that the out-of-plane thermal excursions in a graphene membrane lead to strong anharmonic behavior, which allows large deviations from isotropic elasticity. The computed Young's modulus and Poisson's ratio of a sheet with an infinite spatial extent are 0.939 TPa and 0.223, respectively. We also found that graphene sheets with both finite and infinite spatial extent satisfy the Born elastic stability conditions. We extracted the variation in bending modulus with the system size at zero kelvin (0.83 eV) using a formula derived from the Foppl–von Karman approach. When the temperature increases, the Young's modulus of the sample decreases, which effectively reduces the longitudinal and shear wave velocities.